Rapid genotyping of 508G>A (rs3745635) and 1067T>A (rs3894326) of FUT3 by a duplex Eprobe‐mediated melting curve analysis - Soejima, Mikiko; Koda, Yoshiro (Vox sanguinis, 2022)
Background and Objectives Lewis histo‐blood group phenotypes are regulated by the action of FUT3‐encoded α(1,3/1,4)fucosyltransferase and FUT2‐encoded α(1,2)fucosyltransferase. Since Lewis phenotypes are suggested to be associated with various clinical conditions, a method for large‐scale FUT3 genotyping is desirable. In worldwide populations, 508G>A and 1067T>A of FUT3 are two of three common causal single nucleotide polymorphisms for Lewis‐negative alleles. Materials and Methods We developed a duplex Eprobe‐mediated melting curve analysis for genotyping 508G>A and 1067T>A simultaneously and applied this method to 106 Ghanaian and 140 Japanese subjects. Results The results of both 508G>A and 1067T>A genotyping by duplex Eprobe‐mediated melting curve analysis were completely in agreement with the results of a DNA sequence analysis in 106 Ghanaians and polymerase chain reaction‐restriction fragment length polymorphism analysis in 140 Japanese subjects. Conclusion The present duplex Eprobe‐mediated melting curve analysis is valid and credible for large‐scale estimation of Lewis‐negative alleles.